Interbank interest rates: Funding liquidity risk and XIBOR basis spreads - Gallitschke, Janek; Seifried (née Müller), Stefanie; Seifried, Frank Thomas (Journal of Banking & Finance, 2017)
This article presents a theoretical model for interbank money market (XIBOR) rates that endogenously generates the basis spreads that characterize post-crisis fixed income markets: XIBOR-OIS spreads, tenor basis spreads, and the forward basis. Our approach is based on an explicit modeling of interbank cash transactions where interbank credit and liquidity risk are factored in. The framework of this article offers a consistent, arbitrage-free explanation for the emergence of basis spreads. We also demonstrate that funding liquidity is a key determinant of post-crisis XIBOR rates and, in particular, tenor basis spreads.